Pengaruh Citra Merek Terhadap Minat Beli Produk Oriflame Di Kota Manado - Ahmad, Maimun; Tumbel, Tinneke M.; Kalangi, Johny A. F. (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
This study aims to determine whether brand image influences buying interest in Oriflame products in Manado City. This type of research used in this research is quantitative research. The population of this research is the people of Manado City who have used and bought Oriflame products. Sampling using a non-probability sampling technique. In this study, the total population is unknown, so the determination of the sample size of the population using a theory developed from Isac Michael using the Lemeshow formula and based on the results of calculations with the formula, the number of samples in this study amounted to 100 respondents. Validity Test uses the Product Moment Correlation Technique and the Reliability Test uses the Cronbach Alpha formula. Based on the results of the regression analysis, this is seen from the results of the hypothesis test, the influence of this brand image is the positive significance with a sig value of 0,000 meaning that if the brand image is getting better it will increasingly lead to or encouragement of buying interest. Based on the results of the determinant coefficient, the amount of R Square adjust is 0.382. The results of this statistical calculation mean that the ability of the independent variable in explaining the variation of the dependent variable changes by 38.2%, while the remaining 61.8% is explained by other factors outside the regression model analyzed. From this study, it can be concluded that brand image has a positive effect on buying interest.